Behind the Youtube Addiction and Online Stickiness. Does Fear of Missing Out Count? - Beril Durmuş; Hüseyin Ekizler; Murat Bolelli (Istanbul Business Research)
As social media has evolved into a predominant aspect of daily life, with over 5 billion users globally, understanding the motivations behind user engagement is essential. The purpose of this study was to examine the relationships between loneliness, self-esteem, FoMO (Fear of Missing Out), YouTube addiction, and online stickiness concepts. This study hypothesizes that self-esteem and loneliness significantly affect FoMO, which in turn influences YouTube addiction and online stickiness. Data were collected from Turkish adults using an online survey tool with convenience sampling method. Confirmatory Factor Analysis, correlation, and path analyses were conducted to test the research hypotheses. The findings indicate positive and significant correlations, as well as the effect of self-esteem on FoMO. Additionally, loneliness was found to be negatively correlated with FoMO Social Experience and positively correlated with FoMO Rewarding Experience, whereas no significant effect of loneliness on both dimensions was found. FoMO Social Experience and FoMO Rewarding Experience were positively correlated with YouTube addiction, and FoMO Social Experience had a significant effect on YouTube addiction. Finally, YouTube addiction is strongly correlated with online stickiness, and its effect on it is significant. The implications of the results are discussed, and future research areas are suggested.